Resilience: Highlighting its Importance for Security and Development through References to (National) Security Strategic Documents of International Actors - Koukakis, Georgios (HAPSc Policy Briefs Series, 2023)
Resilience is a critical capacity for any international actor, allowing it to successfully address emerging challenges in the security environment and to seize opportunities to quickly recover from crises. This article attempts to highlight the importance of resilience for international actors - as far as security and development is concerned - by showing how they have integrated resilience into their targeting through official documents related to (national) security.